The Transformation of corporate social responsibility into legal responsibility - Ffolkes Goldson, Suzanne (2012)
Seeks to look at how the stakeholder model of corporate law has gone beyond the goal of taking into account the interests of a wide group of stakeholders to transforming corporate social responsibility into legal responsibility.